Tuberculous coxitis with trochanteric bursitis manifesting a year after immigration to Germany: a case report - Georgios Sogkas; Anna Holz; Elke Riechers; Florian Länger; Christian von Falck; Reinhold Ernst Schmidt; Torsten Witte (Journal of Medical Case Reports, 2018)
Abstract Background Osteoarticular tuberculosis is rare in Germany. In particular, trochanteric bursitis is an extremely rare manifestation of osteoarticular tuberculosis. We describe a case of tuberculous coxitis with trochanteric bursitis, successfully treated with a fourfold tuberculostatic therapy. Case presentation We report the case of a 43-year-old human immunodeficiency virus-negative Sudanese man with osteoarticular tuberculosis, who was originally admitted with the suspected diagnosis of ankylosing spondylitis. Low grade fever together with the positive result of an interferon-gamma release assay test as well as findings from magnetic resonance imaging provided clues to the diagnosis. A definitive diagnosis could be set after a computed tomography-guided biopsy. Conclusions Apart from a rare involvement pattern of osteoarticular tuberculosis, including trochanteric bursitis, this case highlights the increasing importance of osteoarticular tuberculosis as a differential diagnosis of rheumatic disorders. With the growing migration flows from tuberculosis-endemic African countries, clinicians in central and northern Europe may be more frequently confronted with atypical involvement patterns of osteoarticular tuberculosis.